Differential response of kabuli and desi chickpea genotypes toward inoculation with PGPR in different soils - Imran, Asma; Mirza, Muhammad S.; Shah, Tariq M.; Malik, Kauser A.; Hafeez, Fauzia Y. (Frontiers in Microbiology, 2015)
Pakistan is among top three chickpea producing countries but the crop is usually grown on marginal lands without irrigation and fertilizer application which significantly hampers its yield. Soil fertility and inoculation with beneficial rhizobacteria play a key role in nodulation and yield of legumes. Four kabuli and six desi chickpea genotypes were, therefore, evaluated for inoculation response with IAA-producing Ochrobactrum ciceri Ca-34T and nitrogen fixing Mesorhizobium ciceri TAL-1148 in single and co-inoculation in two soils. The soil type 1 was previously unplanted marginal soil having low organic matter, P and N contents compared to soil type 2 which was a fertile routinely legume-cultivated soil. The effect of soil fertility status was pronounced and fertile soil on average, produced 31% more nodules, 62% more biomass and 111% grain yield than marginal soil. Inoculation either with O. ciceri alone or its co-inoculation with M. ciceri produced on average higher nodules (42%), biomass (31%), grains yield (64%) and harvest index (72%) in both chickpea genotypes over non-inoculated controls in both soils. Soil 1 showed maximum relative effectiveness of Ca-34T inoculation for kabuli genotypes while soil 2 showed for desi genotypes except B8/02. Desi genotype B8/02 in soil type 1 and Pb-2008 in soil type 2 showed significant yield increase as compared to respective un-inoculated controls. Across bacterial inoculation treatments, grain yield was positively correlated to growth and yield contributing parameters (r = 0.294* to 0.838*** for desi and r = 0.388* to 0.857** for kabuli). PCA and CAT-PCA analyses clearly showed a site-specific response of genotype x bacterial inoculation. Furthermore, the inoculated bacterial strains were able to persist in the rhizosphere showing colonization on root and within nodules. Present study shows that plant growth promoting rhizobacteria (PGPR) inoculation should be integrated with national chickpea breading program in Pakistan especially for marginal soils. Furthermore, the study shows the potential of phytohormone producing strain Ca-34T as promising candidate for development of biofertilizer alongwith nodulating strains to get sustainable yield of kabuli and desi chickpea with minimum inputs at marginal land.